Advances in industrial robotics [ - Advanced Productions; Meridian Education Corporation (Bloomington, Illinois : Meridian Education Corporation, 2004)
This video takes a look at the changes that have occured since robotics was first introduced. Students are given a refresher of the basics: terminology, concepts, system components, classification of robots. But then, new applications and work tasks are overviewd. They see how far robotics has advanced industry-wide. Students also discover where robots are commonly used and some anticipated future applications in business and industry. Offer your students critical information on robotics as it plays a more important role in commercial and industrial settings around the world
Originally produced in 1998
This disc is a recorded DVD and may not play on all DVD players or drives
Executive producer, Twila Sears
System requirements:DVD player
English
Keywords: Robotics; Robots; Robots, Industrial